Somatic health, adaptable potential, physical condition and biological age of students of pedagogical college - Romanchishin O.N; Sidorko O.J; Dyka M.V (Kharkov National Pedagogical University, 2010)
Comparative characteristic of health indicators of students of Pedagogical College. Conducted and measurement indicators somatometric and physiometric 545 students 2-4 courses of Pedagogical College. Identification of "dangerous" level indicators of the health of students. Confirmed that the level of physical health and physical mill male students than students. Found that over the years, the College has deteriorated somatic health students, adaptive capacity and physical well-being of students